Исследование тепловых процессов в линейном импульсно-индукционном электромеханическом преобразователе циклического действия - Болюх, В.Ф; Щукин, И.С. (Електротехніка і електромеханіка, 2017)
Разработана математическая модель линейного импульсно-индукционного электромеханического преобразователя
(ЛИИЭП) циклического действия, система уравнений которой учитывает комплекс взаимосвязанных электромагнитных, электромеханических и тепловых процессов. Решения этих уравнений представлены в рекуррентном виде.
Исследованы процессы ЛИИЭП, протекающие при прямом ходе рабочего цикла. Показано, что к концу рабочего цикла
значительная часть энергии сохраняется в емкостном накопителе энергии, а также преобразуется в тепловую энергию якоря и индуктора. При значительном числе рабочих циклов происходит недопустимый нагрев активных элементов ЛИИЭП. Для решения этой проблемы используется интенсивное охлаждение обмотки индуктора, подвижного якоря или их обоих, а также увеличение периода следования импульсов. Установлено, что при работе ЛИИЭП в
циклическом режиме экспериментальные зависимости температуры нагрева обмотки индуктора с точностью до 6
% совпадают с расчетными результатами. Разработана конструктивная схема ЛИИЭП циклического действия с
интенсивным водяным охлаждением обмотки индуктора. Розроблена математична модель лінійного імпульсно-індукційного електромеханічного перетворювача (ЛІІЕП) циклічної дії, система рівнянь якої враховує комплекс взаємопов’язаних електромагнітних, електромеханічних та теплових процесів. Рішення цих рівнянь представлені в рекурентному вигляді. Досліджені процеси ЛІІЕП, що протікають
при прямому ході робочого циклу. Показано, що в кінці робочого циклу значна частина енергії зберігається в ємнісному
накопичувачі енергії, а також перетворюється в теплову енергію якоря та індуктора. При значному числі робочих
циклів виникає недопустимий нагрів активних елементів ЛІІЕП. Для рішення цієї проблеми використовується інтенсивне охолодження обмотки індуктора, рухомого якоря або їх обох, а також збільшення періоду слідування імпульсів.
Встановлено, що при роботі ЛІІЕП в циклічному режимі експериментальні залежності температури нагріву обмотки індуктора з точністю до 6 % співпадають з розрахунковими результатами. Розроблена конструктивна схема
ЛІІЕП циклічної дії з інтенсивним водяним охолодженням обмотки індуктора. Purpose. Investigation of the influence of the intensity of cooling
of active elements and the period of succession of power pulses
on the thermal processes of linear pulse-induction electromechanical converter (LPIEC) operating in a cyclic mode. Methodology. The electromechanical and energy processes of
LPIEC, which arise during the direct course of the working
cycle, are investigated. It is shown that by the end of the operating cycle, a significant part of the energy is stored in the capacitive energy storage device, and is also converted into thermal
energy of the armature and inductor. With a significant number
of operating cycles, an unacceptably high temperature rise of
LPIEC active elements occurs. To solve this problem, intensive
cooling of the winding of the inductor, the movable armature or
both of them, as well as an increase in the pulse repetition period are used. It has been experimentally established that when
the LPIEC is operating in a cyclic mode, the inductor winding
with a steel frame blown with air is heated more slowly than the
winding with an insulating frame. The experimental dependences with an accuracy of 6 % coincide with the calculated
results. A constructive scheme of the LPIEC of cyclic action with
intensive cooling of the stationary winding of the inductor has
been developed. Results. A mathematical model of the LPIEC of
cyclic action is developed, taking into account a complex of
interrelated electromechanical and thermal processes. The
solutions of its equations are represented in a recurrent form.
The electromechanical and energy processes of LPIEC, which
arise during the direct course of the working cycle, are investigated. It is shown that for a considerable number of operating
cycles, unacceptably high temperature excesses of active elements of the LPIEC are observed. It is shown that intensive
cooling of the winding of the inductor, the movable armature or
both of them, and also the increase in the pulse repetition period
ensure the temperature stabilization of the LPIEC. Measurements of the temperature on the surface of the winding of the
inductor LPIEC during cyclic operation are carried out. A
constructive scheme of the LPIEC of cyclic action with intensive
cooling of the stationary winding of the inductor has been developed. Originality. A mathematical model of the LPIEC of
cyclic action is developed, taking into account a complex of
interrelated electromechanical and thermal processes. The
solutions of its equations are represented in a recurrent form. It
is shown that by the end of the working cycle a significant part
of the energy is converted into thermal energy of the armature
and inductor. It is determined that for a significant number of
operating cycles, unacceptably high temperature excesses of
active elements of the LPIEC are observed. It is shown that
intense cooling of active elements, as well as an increase in the
pulse repetition period, ensure the temperature stabilization of
the LPIEC. A design scheme of the LPIEC with intensive cooling
of the stationary winding of the inductor has been developed.
Practical value. It is shown that by thermal cooling of at least
one of the active elements and by increasing the pulse repetition
period, the temperature stabilization of the LPIEC is ensured. A
constructive scheme of the LPIEC of cyclic action with intensive
cooling of the stationary winding of the inductor has been developed.